KEWAJIBAN PERUSAHAAN GO PUBLIC UNTUK MELAKSANAKAN CSR (CORPORATE SOCIAL RESPONSIBILITY) - Dyva Dhamahadi Yadnya, Putu; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013, 2013)
Corporate Social Responsibility, is an act or concept taken by the company(according to the ability of the company), in accordance with what is stipulated in the Law.No. 40 of 2007 which confirmed again by Government Regulation No. settings. 47 of 2012and Law no. 25 of 2007 On Investment. Examples of responsibilities that can be done is anactivity that can improve the livelihoods of the people can be: environmentalimprovements, scholarships, funding for public places, medical assistance, etc., in order toreach a harmonious relationship between the company, shareholder, stakeholder.
Keywords: Responsibility, Company, Shareholder, Stakeholder